(untitled) (Jagannath University Journal of Science, 2024)
Adolescents undergo significant psychological and emotional changes, with factors such as anxiety, emotional intelligence, and self-esteem playing pivotal roles in their regular development, whereas their association is unclear. This study investigates how emotional intelligence plays a role as a moderator between anxiety and self-esteem of Bangladeshi adolescents. The study was conducted by following a cross-sectional study design, whereas a total of 300 high-school students were selected using a random sampling technique. Data were collected using the Bangla version of anxiety, emotional intelligence, and self-esteem measuring questionnaires. The results displayed that in the case of anxiety, emotional intelligence, and self-esteem, no significant differences were found across varied socio-economic statuses, while these three outcome variables were significantly varied due to gender and family types. In addition, the Pearson product-moment correlation explored a significant negative correlation of anxiety with emotional intelligence and self-esteem and a positive correlation between emotional intelligence and self-esteem among students. Furthermore, the hierarchical regression analysis manifested buffering effects of emotional intelligence in the relationship between anxiety and self-esteem. This study’s findings emphasize the importance of emotional intelligence in mitigating anxiety and enhancing self-esteem, regardless of varied socio-economic status. Ultimately, the findings would contribute to policy and decision-making regarding improving the well-being of adolescents in Bangladesh. Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 94−105